Encounters with world affairs an introduction to international relations (Routledge, 2016)
This book is designed to familiarise students with leading International Relations (IR) theories and their explanation of political events, phenomena, and processes which cross the territorial boundaries of the state. Thus, students will be exposed to the interplay between power, interest, ideas, identity, and resistance, in explaining continuity and change in international relations. Developed to provide students with the analytical tools and intellectual frameworks needed to understand the behaviour of different international actors in contemporary global affairs. This textbook responds to the challenges of a dynamic job market by assisting students to gain both thorough theoretical knowledge and training them to apply this knowledge to real world problems. In short, this textbook delivers: A comprehensive and interdisciplinary approach to the examination of national, regional and global trends in politics, economics and socio-cultural developments allowing students to understand: • the practice and theory of contemporary international relations • the politics, culture, history, and economies of different regions around the world • the role played by international interactions, culture, and government in local, national, and global settings. Equipping students with the proficiency: • to understand and interpret the dynamics, patterns, and issues of global affairs • to know how to get more information about particular questions • to evaluate that information independently and effectively. To these ends, the textbook provides a number of features that will appeal to students and avoids overwhelming students with chapters on topics which (in practice) are rarely on courses, while nonetheless providing a comprehensive overview of the field. Introduces students to the main debates, topics, and terms in the field and allows them to decide which they would like to focus on in their further studies.